Autonomous Self Check-In KeyBox and Reservation for Homestay Operation - Faizon, Wan Muhammad Ezzadam; Nor'aisah Sudin (Evolution in Electrical and Electronic Engineering, 2023)
Homestay check-in procedure usually requires physical interaction between owner and guests for registration along with key issuance to the guest. Sometimes, homestay owner are not available and not able to physically meet-up with guest to issue keys. Moreover, with recent Covid-19 outbreak, people are encouraged to minimize physical interaction to subdue the outbreak of Covid-19. To automate reservation and check-in process of homestay operation while also minimize physical interaction between owner and guest, an Autonomous Self Check-In KeyBox and Reservation for Homestay Operation is developed. There are three main components in the system which are reservation form, admin webpage and KeyBox. This project is focused on providing a web-based system which developed using HTML, PHP and MariaDB while KeyBox is developed using NodeMCU ESP32. To integrate different platform, uses of Application Programming Interface (API) and Relational Database Management System (RDMS) is required to allow interaction between platforms. The designed system able automize reservation and check-in process while also minimize physical interaction between homestay owner and guest